Could a Personalized Strategy Using Accelerated Partial Breast Irradiation be an Advantage for Elderly Patients? A Systematic Review of the Literature and Multidisciplinary Opinion. (28th February 2020) - Tagliaferri, Luca; Lancellotta, Valentina; Colloca, Giuseppe; Marazzi, Fabio; Masiello, Valeria; Garganese, Giorgia; Kovács, György; Valentini, Vincenzo; Gambacorta, Maria Antonietta
Abstract : Introduction . Elderly patients are underrepresented from a majority of clinical trials and the choice of the best treatment becomes a challenge. The optimal treatment should be personalized and based on a multidisciplinary approach that includes radiation oncologists, surgeons, geriatricians, medical oncologists, social workers, and support services. The global evaluation of the patients and the creation of nomograms may facilitate the definition of long-term treatment benefits minimizing the use of unnecessary therapy. Material and Method . A systematic research using PubMed, Scopus, and Cochrane library was performed to identify full articles analyzing the efficacy of APBI in elderly patients with breast cancer. ClinicalTrials.gov was searched for ongoing or recently completed trials, and PROSPERO was searched for ongoing or recently completed systematic reviews. Results . Seven papers fulfilled the eligibility criteria. The number of evaluated patients was 405 and the median age was 77.7 years. The disease-free survival (DFS) range was 96.1%–100%, the grade 3-4 toxicity range was 0%–6.6%, the cancer-specific survival (CSS) range was 97.9%–100%, and the overall survival (OS) range was 87%–100%. All studies reported excellent/good cosmetic results in a range of 74% to 99%. Conclusion . Accelerated partial breast irradiation (APBI) results in a safe and effective substitute for the adjuvant external beam radiotherapy in selected elderly early-stage breast cancer patients. Based on the relatively low toxicity, APBI should be advised in selected patients with life expectancies larger than 5–10 years.